FATP5 modulates biological activity and lipid metabolism in prostate cancer through the TEAD4-mediated Hippo signaling - Liu, Shenyang; He, Yi; Gu, Zhengqin (Frontiers in Oncology, 2024)
Prostate cancer ( PCa ) , one of the most prevalent malignant tumors in the genitourinary system, is characterized by distant metastasis and the development of castration-resistant prostate cancer (CRPC), which are major determinants of poor prognosis. Current treatment approaches for PCa primarily involve surgery and endocrine therapy, but effective strategies for managing distant metastasis and CRPC remain limited. In this study, we conducted an analysis of clinical samples and public databases to identify differential expression of FATP5 and further investigated its association with clinical outcomes. Through biochemical and functional experiments, we elucidated the potential underlying mechanisms by which FATP5 facilitates the progression of PCa. Our findings demonstrate that specific upregulation of FATP5 significantly enhances proliferation, migration, and invasion of PCa cell lines, while also modulating lipid metabolism in PCa. Mechanistically, the expression of FATP5 is closely associated with the Hippo signaling pathway, as it promotes the nuclear accumulation of YAP1 by inhibiting AMPK and facilitating the activation of β-catenin and RHOA. Furthermore, the transcription of FATP5 is mediated by TEAD4, and this transcriptional activation requires the involvement of YAP1.Therefore, our study suggests that targeting FATP5 or TEAD4 may represent attractive therapeutic targets for PCa.